A Review of Digital Image Classification Based on Fuzzy Logic - Sinambela, Marzuki; Rahayu, Teguh; Darnila, Eva; Limbong, Tonni (MEANS (Media Informasi Analisa dan Sistem), 2020)
Fuzzy logic has long been an important issue for in the field of computer science, computer vision, image processing, machine learning and control theory and mathematics. In this review paper, we also see that the basics of fuzzy logic as well as fuzzy logic system (Fuzzy Inference System) use as decision making technique under a linguistic view of fuzzy sets. In this study, we focused to review the fuzzy logic to classification of digital image. The aim of this study was to review the fuzzy logic algorithm for classification of image.